The synthesis and properties of the phases obtained by solid-solid reactions - Blonska-Tabero A.; Bosacka M.; Dabrowska G.; Filipek E.; Piz M.; Rychlowska-Himmel I.; Tabero P.; Tomaszewicz E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The presented work encompasses the subject of the studies and the results obtained over the last years by the research workers of the Department of Inorganic Chemistry. They include mainly the studies on the reactivity of metal oxides, searching for new phases in binary and ternary systems of metal oxides as well as describing phase relations establishing in such systems. They also encompass works on the extensive characteristics of physico-chemical properties of the newly obtained compounds.